Reading Instructions Influence Cognitive Processes of Illustrated Text Reading Not Subject Perception: An Eye-Tracking Study - Jian, Yu-Cin (Frontiers in Psychology, 2018)
Scientific illustrations play an important role in scientific texts, however, young readers show limited ability to use illustration information and integrate it with the text in multimedia learning. The primary goal of the present study was to investigate if strategy instructions for illustrated text reading focused on scientific illustration reading and text-illustration integration can help young readers overcome their deficiencies and change their reading processes, learning outcomes, and subjective perceptions of article difficulty and enjoyment, illustration enjoyment, and self-evaluation of learning. Besides, is subjective perception of the article related to reading behavior? Sixty-two fourth-grade students read an illustrated science text while their eye movements were recorded, and then completed a reading test and questionnaire. The instruction group outperformed the control group on the reading test, but subjective perceptions of the article did not differ between groups. Eye-movements analysis showed that the instruction group spent twice as much time reading the illustrations and made more saccades between relevant text and illustration sections than the control group. These findings indicate that strategy instructions for reading illustrated text promoted reading comprehension and changed learning processes, not subjective perceptions. In addition, the result of this study showed that there was no relationship between subjective perception (article difficulty or illustrations enjoyment) of the article and reading time (total reading time on the illustrated science text and on the science illustrations). This study had empirical and practical contributions. Empirically, this study developed the instruction methods in multimedia learning and further examined their effect on learning processes in young readers. Practically, this study can help elementary school teachers understand the processes used by young readers when reading illustrated texts and provide them with evidence-based instructions to teach science reading effectively.